Analisis SEO Marketing terhadap Pemasaran Internasional pada Promosi Dagang Asia (Promosia) - Golan Hasan; Alzi; Miftachul Choiri; Brahmantya Chriswardhana; Jimmy Tjong (Universitas Haji Sumatera Utara, 2024)
Digital marketing is one of the determining factors for the sustainability of a company. Digital marketing is considered efficient and effective for companies in their efforts to reach consumers. One of the digital marketing methods is using a website that aims to display the company profile, types of activities, and what can be offered to consumers. The website serves as a digital marketing medium because it can be accessed online by anyone, anywhere. However, a website also requires regular optimization and development to appear on the main pages of search engines. Therefore, search engine optimization (SEO) is needed to help improve the quality of the website and assist it in appearing on the main pages of search engines, thereby enhancing the niche of a company's profile on the website. This study focuses on the implementation of SEO and its impact analysis on an international export company, namely Promosi Dagang Asia (Promosia). The implementation is carried out using agile methods, and the main goal of this research is to determine the extent of the influence of SEO on the Promosia website.